Estudo das propriedades magnéticas do LaCrO3 dopado com Sr e Mn - Fontes, José Fernando Dutra (2015)
Oxides with perovskite structure have been objects of intense study since their discovery in 1839 and are still being widely studied due to richness and diversity of physical properties present in these materials, including a wide range of important magnetic properties both from a scientific point of view as technological. It is known that the magnetic properties of these materials are very sensitive to the effects of substitution of chemical doping elements and their structure as well as the preparation method used to obtain it. In this work, we do a detailed study of the effects of heat treatment on structural and magnetic properties of the compound pure and doped LaCrO3 with Sr and Mn. The compounds studied here were obtained by the combustion method. It was possible by XRD measurements to identify peaks of desired phase on some samples after combustion. However, heat treatments were conducted at 300 ° C / 1h, 400 ° C / 1h, 500 ° C / 1h, 600 ° C / 1h, 700 ° C / 1h and 800 ° C / 1h in order to eliminate the peaks of the secondary phases and to evaluate the effects of heat treatment on structural and magnetic properties. Through the magnetization as a function of temperature and the magnetic field can be seen that the inclusion of Sr and Mn induces an increase in spontaneous magnetization at 5K and may lead to positive values Weiss temperature, suggesting a shift in antiferromagnetic (AFM ) order present in LaCrO3 compound to a ferromagnetic order (FM). We also show a large dependence of the magnetic properties of these materials with annealing temperature.